Haptophyte and thaumarchaeal proxy data at monthly to quarterly resolution from Santa Barbara Basin sediment via mass spectrometry imaging - Alfken, Susanne; Wörmer, Lars; Lipp, Julius S; Wendt, Jenny; Schimmelmann, Arndt; Hinrichs, Kai-Uwe (PANGAEA, 2020)
Molecular biomarker data from two sets of compounds used as paleo sea surface temperature proxies - long-chain alkenones from haptophytes and isoprenoidal tetraethers from planktonic archaea - were measured with the extraction-free approach of MALDI FT-ICR-MS in annually varved sediments from the Santa Barbara Basin deposited from AD 1984 - 2009.
Keywords: Mass spectrometry imaging; Santa Barbara Basin box core SPR0901-05BC; Sea surface temperature proxy; varves